The effects of load and velocity on friction and interface temperature of CGRP sliding against smooth stainless steel - Yousif B.F.; El-Tayeb N.S.; Yusaf T.F. (American Society of Mechanical Engineers, 2023)
This paper presents an experimental investigation to study friction and interface temperature characteristics of chopped strand mat fiberglass (type-R) reinforced polyester (CGRP) sliding against smooth stainless steel. Pin-on-disk (POD) apparatus is used to perform the experimental tests under dry sliding condition at room temperature. Several parameters are considered, namely load (30, 60 & 90N), sliding velocity (2.8, 3.52 & 3.9m/s) and sliding distance (0-2.51km). Three different orientations of chopped strand mat with respect to sliding direction, Parallel (P), Anti-parallel (AP) and Normal orientations (N) are investigated. Continuous measurements of friction forces using strain gauges, and interface temperatures using infrared thermometer are performed. In addition, Scanning electron microscopy (SEM) is used to study the worn surface to verify the results. Experimental results show that specimen's orientations and the tested parameters play a major role in controlling friction and interface temperature characteristics of the CGRP/stainless steel. Maximum friction coefficient was taken place in AP orientation at 3.5 m/s and 2.5km, which was about 0.6. Although, AP-orientation had higher friction interface temperature in comparing to P and N-orientations, which was about 48C at 3.9m/s and 2.5km. Copyright 2006 by ASME.